Pemanfaatan Hutan Desa dalam Bisnis Furniture - Niami, Sukron; Hendri, Zul (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the potential and strategies for utilizing village forests as local resources in developing sustainable furniture businesses. Village forests, as a form of community-based forest management, have an important role in supporting the local economy while preserving the environment. Using a descriptive qualitative approach, data were collected through in-depth interviews, field observations, and documentation studies in one of the villages that has utilized village forests for furniture production. The results of the study indicate that the utilization of village forests has contributed significantly to increasing community income, creating jobs, and strengthening local business capacity. However, challenges are still faced related to the legality of wood utilization, access to wider markets, and the lack of business management and product design training. Therefore, collaboration between the community, government, and the private sector is key to realizing a furniture business model that is based on local resources and oriented towards sustainability. This study is expected to be a reference in formulating policies for managing productive and environmentally friendly village forests.